HUBUNGAN STRATEGIS MANAJEMEN SDM DALAM BIDANG USAHA KECIL MEBEL KAYU BAKTI SETIA - Maria Silvana Mariabel Carcia; Yoaclinus De Royan Gilo Ipir; Pancrasius Carleandro Lera (JPMNT JURNAL PENGABDIAN MASYARAKAT NIAN TANA, 2026)
This study aims to analyze the strategic relationship of human resource management (HRM) in improving the productivity and competitiveness of the Bakti Setia small-scale wooden furniture business. Small furniture enterprises play an important role in supporting regional economic growth and employment opportunities. However, many small businesses face challenges in human resource management, such as low workforce skills, lack of training, and minimal structured management systems. This research employed a qualitative descriptive method with data collection techniques through observation, interviews, and documentation. The results of the study indicate that the implementation of HRM strategies, including recruitment, job training, motivation, work discipline, and reward systems, has a significant relationship with increased business productivity. In addition, good communication between business owners and employees also influences work effectiveness and the quality of the furniture products produced. This study concludes that effective human resource management strategies can enhance the sustainability of the Bakti Setia small-scale wooden furniture business.